Management of Large Wood in Streams: An Overview and Proposed Framework for Hazard Evaluation1. (7th February 2016) - Wohl, Ellen; Bledsoe, Brian P.; Fausch, Kurt D.; Kramer, Natalie; Bestgen, Kevin R.; Gooseff, Michael N.
Abstract: Instream and floodplain wood can provide many benefits to river ecosystems, but can also create hazards for inhabitants, infrastructure, property, and recreational users in the river corridor. We propose a decision process for managing large wood, and particularly for assessing the relative benefits and hazards associated with individual wood pieces and with accumulations of wood. This process can be applied at varying levels of effort, from a relatively cursory visual assessment to more detailed numerical modeling. Decisions to retain, remove, or modify wood in a channel or on a floodplain are highly dependent on the specific context: the same piece of wood that might require removal in a highly urbanized setting may provide sufficient benefits to justify retention in a natural area or lower‐risk urban setting. The proposed decision process outlined here can be used by individuals with diverse technical backgrounds and in a range of urban to natural river reaches so that opportunities for wood retention or enhancement are increased.